Mode Interaction in Wide Plate with Closed Section Longitudinal Stiffeners Under Compression - Kołakowski, Z. (Engineering Transactions, 1987)
Interaction of nearly simultaneous buckling modes in the presence of imperfections is studied. The investigation is concerned with an infinitely wide plate having thin-walled longitudinal stiffeners of trapezoid cross-section under uniform compression. In these structures a few, modes are of particular interest, namely an overall long-wave buckling mode of the whole structures and local short-waves buckling modes, respectively. The asymptotic expansion established by BYSKOV and HUTCHINSON [1] is also used here. The present paper is devoted to the study of equilibrium paths in the advanced post-buckling region of an imperfect stiffened plate. The bifurcation stress is determined analytically and the asymptotically exact expansion is obtained for the initial post-bifurcation behaviour. The calculations are carried out for several types or plates with closed section longitudinal stiffeners.